Quasi-markets, accountability, and innovation: analyzing the case of Free Schools in England through teachers’ perspectives - Esper, Tomas (Revista Española de Educación Comparada, 2022)
Since 2010, England has undergone a new education reform under quasi-market principles combined with high school autonomy and accountability. Through the Academies and Free Schools policy, almost half of English schools have been transferred to private hands (GOV.UK 2022), fostering school competition with the expectation that private providers would yield innovation (Greany & Higham, 2018). In this exploratory research, I study three Free Schools, a new school type from which innovations are expected (DfE, 2010), looking at what innovations were developed and how teachers make sense of and enacted the competing demands of innovation and accountability. I analyze school innovations using the OECD (2014) framework while I draw on policy enactment literature (Ball et al., 2012) to understand teachers’ views and responses on innovation and accountability. Primary data includes school documents and websites, inspection reports, and interviews with twelve teachers. Findings show wide use of innovative marketing strategies to appeal to parents, but more limited curriculum and pedagogical innovations. Furthermore, teachers’ autonomy and innovative practices are largely mediated by the school culture and leadership views on accountability demands. In line with prior research on quasi-market reforms, high-stakes accountability acts as a main constraint to school autonomy and innovation (Lubienski, 2009b).